Report of a Vegetables Network: Third meeting, 10-12 November 2009, Catania, Italy - Maggioni, L.; Daunay, Marie-Christine; Dooijeweert, W. van; Astley, D.; Bas, N.; Branca, F.; Díez Niclós, M.J.; Geoffriau, E.; Keller, J.; Kotlińska, T.; Smékalová, K.; Treuren, R. van; et al. (2010)
The Third Meeting of the ECPGR Vegetables Network was hosted by the University of Catania in Sicily, Italy, on 10-12 November 2009. About 60 representatives of the six ECPGR Vegetables Working Groups (WGs) gathered from 30 countries to discuss about cooperative action for vegetable genetic resources conservation and use. The main focus of the meeting was on the initiative for “A European Genebank Integrated System” (AEGIS). The general concepts of AEGIS – the Strategic Framework, the Memorandum of Understanding, the Most Appropriate Accessions (MAAs) and A Quality Management System for AEGIS (AQUAS) – were presented and discussed. All WGs intend to make progress in the implementation of AEGIS and this requires quality data in the databases. Therefore, efforts will be made to complete the Central Crop Databases as well as include missing data into EURISCO. Efforts to identify MAAs will focus, as a priority, on leek and wild alliums, lettuce and spinach, carrot, melon, Brassica rapa and various Solanaceae crops. A general consensus was expressed by the group about the principles of AQUAS, and the need to reach pragmatic solutions when it comes to defining common standards. Activities specific to each WG were also presented.